Synthesis of SnO2 nanoribbons by a carbothermal reduction process - Leite, E. R.; Gomes, J. W.; Oliveira, M. M.; Lee, EJH; Longo, Elson [UNESP]; Varela, José Arana [UNESP]; Paskocimas, C. A.; Boschi, T. M.; Lanciotti, F.; Pizani, P. S.; Soares, P. C. (Amer Scientific Publishers, 2002)
This communication describes, for the first time, the growth of SnO2 nanoribbons by a controlled carbothermal reduction process. An analysis of the transmission electron microscopy image revealed that these nanoribbons have a well-defined shape, with a typical width in the range of 70-300 nm. In general, the nanostructured ribbons were more than 100 mum in length. The results reported here support the hypothesis that this ribbon-like nanostructured material grows by a vapor-solid process. This study introduces two hypotheses to explain the SnO2 nanoribbon growth process.
Keywords: SnO2 nanoribbons; carbothermal reduction process.